Riding the emotional roller-coaster: Using the circumplex model of affect to model motorcycle riders' emotional state-changes at intersections. (October 2019) - Samuel, Olugbenga; Walker, Guy; Salmon, Paul; Filtness, Ashleigh; Stevens, Nicholas; Mulvihill, Christine; Payne, Sarah; Stanton, Neville
Highlights: There is an affective dimension to motorcycle riding. Riders' emotions demonstrate a high degree of emotional dynamism and transits from one state to the other. Riders commonly transit from negative affective states to positive ones. Much of these transitions occur in and out of the positive dominant affective state of calmness. Abstract: This study uses Russell's Circumplex Model of Affect to examine whether motorcycle rider emotion is contingent on the environment and behavior. If it is contingent then it becomes predictable. If it is predictable it becomes potentially usable for innovating new ways to improve the safety and utility of this important transport mode. Eighteen motorcyclists took part in a 15 km on-road study during which they were videoed, tracked via GPS, and followed by a 'chase vehicle' as they negotiated intersections, all the while providing a concurrent verbal commentary. The verbal commentary was content analysed using a novel method for mapping the verbalized emotional themes to the Circumplex Model. Network analysis was then used to explore the state changes between affective zones in the model. Riders' emotions at intersections were found to vacillate between negative and positive affect, demonstrating high degrees of emotional dynamism. Many of these transitions occur in and out of the dominant positive state of calmness, with non-calm states appearing to be aversive and those which riders were seeking to avoid. Knowing this brings forward interesting new approaches for safe intersection design.